Molecular Identification of Acidophilic Manganese (Mn)-Solubilizing Bacteria from Mining Effluents and Their Application in Mineral Beneficiation. Issue 1 (2nd January 2017) - Sanket, A. S.; Ghosh, S.; Sahoo, R.; Nayak, S.; Das, A. P.
ABSTRACT: The study of the microbial ecology in extreme acidic environments has provided an important foundation for the development of mineral biotechnology. The present investigation reports the isolation, identification and molecular characterization of indigenous manganese (Mn) solubilizing acidophilic bacterial strains from mine water samples from Odisha, India. Four morphologically distinct bacterial strains showing visible growth on Mn-supplemented plates of varying pH were isolated and identified. Mn solubilizing ability of the isolates was tested by growing them on Mn-supplemented agar plates. The appearance of lightening around the growing colonies of all the isolates demonstrated their Mn solubilizing ability in the medium. 16 S rRNA sequencing was carried out and the bacterial isolates were taxonomically classified as Enterobacter sp . AMSB1, Bacillus cereus AMSB3, Bacillus nealsonii AMSB4 and Staphylococcus hominis AMSB5. The evolutionary timeline was studied by constructing neighbor-joining phylogenetic trees. The ability of acidophilic microorganisms to solubilize heavy metals is supported by five basic mechanisms which include: enzymatic conversion, metal effluxing, reduction in sensitivity of cellular targets, intra- or extracellular sequestration, and permeability barrier exclusion. Such ecological studies undoubtedly will provide insights into Mn biogeochemical processes occurring in leaching environments. The application of acidophilic microbiology in mineral biorecovery and beneficiation has a large future potential.